Re: Completing all the M&E design immediately to be reviewed by Transsolar - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the completion of M&E design immediately to be reviewed by Transsolar for BRACU new campus project.